Relativity of Electric Quantity - GAO Zhong-wen (Journal of Harbin University of Science and Technology, 2017)
The demonstration foundation，which is used to demonstrate that observed values from the interaction force between two charges，which are not at the same point would be different in different reference frames，is that the transmission of the interaction between charges needs time. Firstly，this paper analyzes the foundation of hypothetical process that the electric field and the magnetic field are built by one charge，and then the electromagnetic field would be transferred to another charge in vacuo by the speed of light，and produces force. It points out that from the simultaneity of relativity，the force applied to charge would occur in different time in the different reference frames，the force would be neither in the same size nor in the opposite direction，and Newton’s Third Law is not valid longer, the deeper cause of these conclusions would be known. On this basis，this paper gives the basis that force would keep invariant in different reference frames，and according to this condition，with the situation of the charge that under the Coulombian force and electromagnetism，the relative form of expression and demonstration methods of electric quantity in different reference frames are given. On the basis of the hypothesis that force would keep invariant in different reference frames，with the similar derivation process，the mass relativity equation of Einstein would be obtained.